The Development of an Ergonomic-Based Roadmap for Improving Passenger Mobility Onboard Intercity Trains in Indonesia - Lukman Septaekwara Sihman; David Hitchcock; Kimberley Harding; Abdul Azis Abdillah (MBI, 2024)
Today in Indonesia, intercity railway service has become an essential part of human mobility and can carry more than 298 million passengers in 2022. It is a reliable service since it can carry many passengers and is a form of time-efficient mode of transport. More and more people are using this service including disabled passengers. They are using the railway to travel between the cities. The railway industry has changed a lot in recent years. If we look at the 90s and before, traveling by train was almost entirely used by non-disabled people and very few of the passengers are people with disabilities. It has now changed while some disabled passengers used the rail, and it created some issues for the industry. This service for disabled passengers is a part of Equality, Diversity, and Inclusion (EDI) and the Author found a mismatch between what the disabled passenger wanted and what the industry responded to. This research will try to understand what is happening in the Indonesian railway industry, compare it with the same issue in another country like the United Kingdom (UK), and what or how to get the ideal design and service for intercity onboard service for disabled passengers. This research uses the triangulation ergonomic principle which consists of measurement, observation, and consultation to combine a literature study and interviews with representatives of 4 stakeholders in the Indonesian railway: 1) A regular user of disabled passenger; 2) Executive Director of one of the Indonesian disability passengers Organization; 3) Traffic coordinator of the Directorate General of Railway (DGR) in the Indonesian Ministry of Transport; 4) A Vice President of the Passenger Division from PT. Kereta Api Indonesia (Persero)/KAI, an intercity railway operator. This interview is then combined with the data from the literature study then analyzed with several methods like Quality Function Deployment (QFD) to get the ideal coach design, Communication-Persuasion Matrix theory to address the communication gap between the parties and make an ideal roadmap solution with phasing approach.